(untitled) (Nóema, 2017)
Laruelle has been and still is one of contemporary philosophy’s great mysteries. Excluding the very recent recovery of laruelleian thought by some members of the so-called speculative realist movement, Laruelle’s work has always maintained, in the contemporary continental philosophy’s canon, a position that oscillates between total absence and marginality. Nonetheless, in the recent past, no one has been capable of conceptualizing, in such a precise and radical way, the relationship that unites the philosophical praxis, with all its styles and its instruments, and the way in which philosophy articulates and describes the world. In our work, we will try to retrace the footsteps of laruelleian thought, trying to highlight how, for Laruelle, the ontological problem is inseparable from a constant repetition of the question concerning the methods and the instruments involved. Examining the immanentist ontology and the critique of the philosophical method put forth by Laruelle, we will try to demonstrate how the philosophical investigation concerning the real must undergo the scrutiny of the question: «What are we doing when we talk about the real?»